Need for Achievement an Antecedent for Risk Adaptiveness among Entrepreneurs (Global Journal of Management and Business Research, 2012)
The research presents a descriptive study with empirical evidence which enquired the association between need for achievement and risk Adaptiveness among entrepreneurs. Study explores the fact, how need for achievement appetite ignites the desire for risk taking among entrepreneurs. For the purpose of survey a sample of 100 entrepreneurs, 50 each from small and large scale enterprises, were taken. Results of study exhibited that need for achievement was major factor to influence the degree of risk Adaptiveness among entrepreneurs. Mean value for Risk Adaptiveness among small scale entrepreneurs was (M = 14.86) whereas for large scale entrepreneurs was (M = 22.68). It was clear from the mean value of Risk Adaptiveness that the large scale entrepreneurs were more adaptive to the risk in comparison to small scale entrepreneurs. These findings have also been supported by the t value (t = 9.391, p lt; 0.01).
Keywords: Risk Adaptiveness; Need for Achievement; Entrepreneurs